Artificial Neural Network-aided Mathematical Model for Predicting Soil Stress-strain Hysteresis Loop Evolution - Bocheńska, Marta; Srokosz, Piotr Emanuel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study presents a novel approach to forecasting the evolution of hysteresis stress-strain response of different types of soils under repeated loading-unloading cycles. The forecasting is made solely from the knowledge of soil properties and loading parameters. Our approach combines mathematical modeling, regression analysis, and Deep Neural Networks (DNNs) to overcome the limitations of traditional DNN training.
Keywords: deep neural networks; hysteresis loops; mathematical modeling; soil stress-strain curves; cyclic loading